Glial interactions in the formation and plasticity of the corpus callosum - Czyrska, Joanna; Ziętek, Marta Marlena; Bernat, Agnieszka; Sampino, Silvestre (Frontiers in Cellular Neuroscience, 2025)
The corpus callosum (CC) is the largest interhemispheric commissure in the eutherian brain, enabling inter-hemispheric sensory integration and higher-order cognitive functions. Historically viewed through a neuron- and axon-centric lens, extensive research has established that glial cells (astrocytes, oligodendrocytes, and microglia) are essential regulators of CC ontogenesis. Astrocytic guidepost cells sculpt midline architecture and secrete axonal guidance cues; oligodendrocytes drive callosal axonal maturation and myelination; and microglia regulate their fasciculation and pruning, myelination patterns, and synaptic refinement. In addition to these cell-specific roles, coordinated bidirectional signaling between neurons and glia ensures that axon targeting, maturation, and interhemispheric integration proceed in a precisely orchestrated manner. Disruptions to these glial functions are implicated in congenital and developmental brain pathologies, including malformations and CC agenesis. This review integrates molecular, developmental, and translational insights to provide a comprehensive, mechanistic understanding of glial contributions to CC development and how their dysfunction shapes pathology.